Peran Emosi Dalam Proses Belajar - Isniarty Gintulangi (Departement of Mathematics Education, 2024)
This study aims to analyze the role of emotions in the learning process of students. The method used in this research is a literature review. In this literature review, the data sources used are derived from academic journals, articles, and research reports published in the last 10 years, from December 2014 to December 2024. The search in this study utilized one database, Google Scholar. The search keywords used were